Laser assisted extraction of pacemaker and implantable defibrillator leads - Costa,Roberto (2001)
OBJECTIVE: To analyze the results of laser-assisted extraction of permanent pacemaker and defibrillator leads. METHODS: We operated upon 36 patients, whose mean age was 54.2 years, and extracted 56 leads. The reasons for extracting the leads were as follows: infection in 19 patients, elective replacement in 13, and other causes in 4 patients. The mean time of catheter placement was 7.5±5.5 years. Forty-seven leads were from pacemakers, and 9 were from defibrillators. Thirty-eight leads were in use, 14 had been abandoned in the pacemaker pocket, and 4 had been abandoned inside the venous system. RESULTS: We successfully extracted 54 catheters, obtaining a 96.4% rate of success and an 82.1% rate for complete extraction. The 2 unsuccessful cases were due to the presence of calcium in the trajectory of the lead. The mean duration of laser light application was 123.0±104.5 s, using 5,215.2±4,924.0 pulses, in a total of 24.4±24.2 cycles of application. Thirty-four leads were extracted from the myocardium with countertraction after complete progression of the laser sheath, 12 leads came loose during the progression of the laser sheath, and the remaining 10 were extracted with other maneuvers. One patient experienced cardiac tamponade after extraction of the defibrillator lead, requiring open emergency surgery. CONCLUSION: The use of the excimer laser allowed extraction of the leads with a 96% rate of success; it was not effective in 2 patients who had calcification on the lead. One patient (2.8%) had a complication that required cardiac surgery on an emergency basis.